Pole Approximation for pion electromagnetic form factor within light-front dynamics - De Melo, J. P.B.C. [UNESP]; Veiga, J. S.; Frederico, T.; Pace, E.; Salmé, G. (World Scientific Publishing, 2007)
We carefully investigate the reliability of the propagator Pole Approximation, i.e. the approximation of retaining only the propagator poles in the evaluation of the Mandelstam covariant expression for the electromagnetic current of the pion. Different frames are analyzed, in order to find the most suitable one for calculating the pion form factor within the proposed approximation. It turns out that the approximation is more accurate in the frame where q+ is maximal. The relevance of the Pole Approximation is briefly discussed in view of calculations of hadron form factors based on wave functions generated by dynamical models.
Keywords: Electromagnetic form factor; Light-front; Quark model